Direct oxidative dearomatization of indoles: access to structurally diverse 2, 2-disubstituted indolin-3-ones. Issue 46 (20th May 2019) - Liu, Xigong; Yan, Xue; Tang, Yingde; Jiang, Cheng-Shi; Yu, Jin-Hai; Wang, Kaiming; Zhang, Hua
Abstract : Described is an efficient oxidative dearomatization of indoles with TEMPO oxoammonium salt and a broad range of nucleophiles. Abstract : Described is an efficient oxidative dearomatization of indoles with TEMPO oxoammonium salt and a broad range of nucleophiles. Under very mild conditions, dearomative oxyalkynylation and oxyalkenylation of indoles to structurally diverse 2, 2-disubstituted indolin-3-ones were developed for the first time with high atom-economy. In addition, dearomative oxyarylation, oxyallylation, and oxycyanation of indoles were also demonstrated. Mechanism studies indicated that TEMPO oxoammonium salt served as the sole oxidant source through an electron donor–acceptor (EDA) intermediate.